1999
DOI: 10.1046/j.1365-2168.1999.01230.x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of primary anastomosis without colonic lavage for patients with an obstructed left colon

Abstract: Emergency surgery on the obstructed left colon can be carried out safely after decompression alone, without intraoperative colonic lavage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
55
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 10 publications
5
55
0
2
Order By: Relevance
“…21 Recent results of series of primary anastomosis in an unprepared bowel, for either malignant or non-malignant colonic obstruction, are encouraging. 22,23 Other operative techniques such as sigmoidopexy and, more recently, percutaneous endoscopic colostomy have been used in the management of recurrent sigmoid volvulus. Promising results have been described for percutaneous endoscopic colostomy in selected patients, although the technique is not wide-spread and has not been employed in our unit.…”
Section: Discussionmentioning
confidence: 99%
“…21 Recent results of series of primary anastomosis in an unprepared bowel, for either malignant or non-malignant colonic obstruction, are encouraging. 22,23 Other operative techniques such as sigmoidopexy and, more recently, percutaneous endoscopic colostomy have been used in the management of recurrent sigmoid volvulus. Promising results have been described for percutaneous endoscopic colostomy in selected patients, although the technique is not wide-spread and has not been employed in our unit.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20][21] This idea was supported by various RCTs comparing mechanical bowel preparation, with no preparation in elective open colonic surgery. The results were separately examined in a Cochrane systematic review of 9 RCTs 22 and in a metaanalysis of 7 RCTs.…”
Section: Primary Resectionmentioning
confidence: 95%
“…Other non-randomised studies or case series have shown manual decompression to be safe. [18][19][20] Although one-stage resection and anastomosis is considered to be a better option than Hartmann's procedure in left-sided colonic obstruction, this is not true for all patients, and other parameters should be examined before choosing the operation. 5,13,24 Patients should be stratified according to risk.…”
Section: Primary Resectionmentioning
confidence: 99%
“…Naraynsingh et al 14 reported only one leak and one postoperative death in 58 consecutive patients with left-sided malignant colonic obstruction who underwent decompression without irrigation, followed by resection and primary colocolic anastomosis.…”
Section: Discussionmentioning
confidence: 99%